(untitled) (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
Reading is a complex cognitive process of decoding symbols for the purpose of deriving meaning (reading comprehension) and constructing meaning. It means that learning reading is significant because it has an aim to understand the meaning of what is read. The researcher should make students interested in the material given because the first semester students of English Department of STKIP PGRI Bangkalan have problem to understand the contents of what is read. Based on the observation, the use of picture series was able to increase students’ skill of reading narrative text. And students could comprehend the narrative text easily. Besides that, it will contribute in making teaching learning of reading more relax, enjoyable, the good response and can avoid from boredom. Third, other researcher, It is suggested to give useful to the next researcher in develop their study especially the using of picture series in teaching reading.